P24 The relationship of truncal, upper and lower limb muscle mass, strength and performance in patients with End-Stage Liver Disease: A UK prospective study. (20th September 2022) - Dhaliwal, Amritpal; Quinlan, Jonathan; Williams, Felicity; Allen, Sophie; Choudhary, Surabhi; Breen, Leigh; Lavery, Gareth; Greig, Carolyn; Lord, Janet; Armstrong, Matthew; Elsharkawy, Ahmed
Abstract : Introduction: End stage liver disease (ESLD) negatively impacts muscle homeostasis with observed reductions in muscle mass (sarcopenia) and strength. The current recommended measures of muscle mass in ESLD are 3rd lumbar vertebral skeletal muscle index (L3 SMI) via CT/MRI and/or the by-the-bedside mid arm muscle circumference (MAMC). However, little is known how well these represent muscle mass and strength in the lower limbs. The aim of this prospective study was to understand how well conventional measures of sarcopenia correlate with measures of lower limb muscle mass and strength in patients with ESLD. Methods: Patients with ESLD underwent: MRI imaging of the trunk (conventional L3 SMI (cm3/m2) and lower limb (quadriceps volume (cm3), quadriceps volume index (cm3/m2), peak quadriceps anatomical cross-sectional area (ACSA (cm2)); ultrasound measured vastus lateralis muscle thickness (cm); MAMC (cm); peak dominant handgrip strength (HGS (kg)), maximal isokinetic leg extension peak torque (Nm) using dynamometry and habitual physical activity via accelerometry. Results: In total 39/42 patients with ESLD cohort (62% male; mean age 55 yrs; MELD 13; Child Pugh 8; ArLD 48%) provided a full dataset. L3 SMI was positively correlated with all lower limb MRI measures of muscle mass (r=0.64–0.68, p<0.01) and ultrasound (R=0.42, p<0.05). L3 SMI correlated with both leg extension peak torque (r = 0.57; p<0.001) and HGS (r = 0.43, p<0.05). All MRI measures of lower limb muscle mass were significantly correlated with measures of lower and upper limb strength ( figure 1 ). Of all modalities, MRI measured quadriceps volume had the strongest correlation with both upper (HGS r= 0.60, p<0.001) and lower limb muscle strength (leg extensor peak torque r= 0.71, p<0.001). MAMC, however, correlated poorly with L3 SMI and all measures of strength, including HGS (r=0.03, p=ns) Conclusion: Unlike MAMC, the conventional use of L3 SMI is an adequate surrogate marker for both lower limb muscle mass and strength. Overall, MRI quadricep volume demonstrated the strongest relationship with both upper and lower limb muscle wasting and weakness. Our findings suggest MRI quadricep volume may be a more suitable assessment tool for muscle compromise in ESLD.